MOOD ANALYSIS IN TEACHER’S SCAFFOLDING TALKS: A STUDY OF INTERPERSONAL MEANING IN ENGLISH CLASSROOM COMMUNICATION - Febrianty, Nur Aisyiah; Rozelin, Diana (University of Kuningan, 2024)
Communication serves as a way to connect with others, share the experiences and needs, and strengthen relationships in everyday life. It enables people to voice their opinions, share knowledge, and express their emotions. People must communicate. Whether people communicate verbally or in writing, it makes decisions about which words to use depending on the situation's field, tone, and modality. More significantly, it is asserted that when teachers have a through awareness of the connection between teacher’s speak, interaction, and learning opportunity in the classroom is frequently improved. This research analyzes the mood of teacher’s scaffolding talk in teaching English subject through interpersonal meaning analysis. The type of this research is descriptive qualitative research. The result of data analysis shows that there are 154 clauses of scaffolding talks analyzed in class A and 147 clauses of scaffolding talks analyzed in class B. The dominant mood system of scaffolding talks in the research subject was declarative mood as it got 55% and 50%. So, it can be concluded that the speech function used in the spoken text is statement which functions to give information.Keyword: mood analysis, teachers’ scaffolding talks, declarative mood, imperative mood.